2021
DOI: 10.1021/acs.nanolett.1c01313
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostrictive-Piezoelectric-Triggered Nanocatalytic Tumor Therapy

Abstract: Magnetic-based theranostics feature a high efficiency, excellent tissue penetration, and minimal damage to normal tissues, are noninvasive, and are widely used in the diagnosis and therapy of clinical diseases. Herein, a conceptually novel magnetostrictive-piezoelectric nanocatalytic medicine (MPE-NCM) for tumor therapy is proposed by initiating an intratumoral magneto-driven and piezoelectric-catalyzed reaction using core–shell structured CoFe2O4–BiFeO3 magnetostrictive-piezoelectric nanoparticles (CFO-BFO NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 38 publications
0
74
0
Order By: Relevance
“…Once ROS generation is inadequate, due to the upregulated antioxidant defense system of tumor cells, the cells may escape or recover from oxidative damage, which may lead to tumor proliferation, recurrence, and metastasis. [3] Recently, to activate the current nanozymes and improve their catalytic activities and therapeutic outcomes, different external stimulators have been locally used to improve the catalytic efficiency, including near-infrared light, [4] ultrasound, [5] magnetic field, [6] microwave, [7] and electricity. [8] With regard to using electricity as a stimulator, natural protein enzymes are considered to have strong and permanent electrostatic fields in their active sites, which are believed to be the major factor responsible for the binding of these enzymes with substrates and subsequent catalytic reactions, namely the electrostatic preorganization effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once ROS generation is inadequate, due to the upregulated antioxidant defense system of tumor cells, the cells may escape or recover from oxidative damage, which may lead to tumor proliferation, recurrence, and metastasis. [3] Recently, to activate the current nanozymes and improve their catalytic activities and therapeutic outcomes, different external stimulators have been locally used to improve the catalytic efficiency, including near-infrared light, [4] ultrasound, [5] magnetic field, [6] microwave, [7] and electricity. [8] With regard to using electricity as a stimulator, natural protein enzymes are considered to have strong and permanent electrostatic fields in their active sites, which are believed to be the major factor responsible for the binding of these enzymes with substrates and subsequent catalytic reactions, namely the electrostatic preorganization effect.…”
Section: Introductionmentioning
confidence: 99%
“…Once ROS generation is inadequate, due to the upregulated antioxidant defense system of tumor cells, the cells may escape or recover from oxidative damage, which may lead to tumor proliferation, recurrence, and metastasis. [ 3 ] Recently, to activate the current nanozymes and improve their catalytic activities and therapeutic outcomes, different external stimulators have been locally used to improve the catalytic efficiency, including near‐infrared light, [ 4 ] ultrasound, [ 5 ] magnetic field, [ 6 ] microwave, [ 7 ] and electricity. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Chemodynamic therapy (CDT), which takes advantage of iron-mediated Fenton reaction or Cu 2+ -/Mn 2+ -mediated Fenton-like reaction to convert less reactive H 2 O 2 into highly toxic ·OH for inducing cell apoptosis and necrosis 1 - 4 , has attracted widespread attention in recent years due to its high selectivity and logicality as well as activation of endogenous stimuli 5 - 9 . To date, despite tremendous efforts have been achieved in triggering tumor cells apoptosis by the endogenous H 2 O 2 -dependent Fenton reaction in CDT 10 - 14 , their therapeutic effectiveness remains a great challenge due to the tumor microenvironment (TME) characterized by insufficient endogenous hydrogen peroxide (H 2 O 2 , 50-100×10 -6 M) 6 , 15 - 17 , overexpressed glutathione (GSH) 18 - 24 as well as hypoxia microenvironment 25 - 32 . Therefore, to potentially enhance their antitumor efficiency, several H 2 O 2 -supplementing strategies have been applied to convey exogenous H 2 O 2 or trigger endogenous H 2 O 2 generation in the tumor site 16 , 33 - 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mushtaq et al (11)(12)(13) reported that BFOcoated CFO (BCFO) can efficiently generate excited charge carriers in response to low-frequency magnetic field (e.g., below 1.1 kHz). Furthermore, the magnetic field-responsive BCFO is biocompatible with human cells [e.g., osteoblasts (12) and neuronal cells (14)] and mouse models (15), hinting at its potential for medical applications.…”
Section: Introductionmentioning
confidence: 99%